Mechanism of the Rpn13-induced activation of Uch37. Issue 8 (22nd April 2014) - Jiao, Lianying; Ouyang, Songying; Shaw, Neil; Song, Gaojie; Feng, Yingang; Niu, Fengfeng; Qiu, Weicheng; Zhu, Hongtao; Hung, Li-Wei; Zuo, Xiaobing; Eleonora Shtykova, V; Zhu, Ping; et al.
Abstract: Uch37 is a de-ubiquitinating enzyme that is activated by Rpn13 and involved in the proteasomal degradation of proteins. The full-length Uch37 was shown to exhibit low iso-peptidase activity and is thought to be auto-inhibited. Structural comparisons revealed that within a homo-dimer of Uch37, each of the catalytic domains was blocking the other's ubiquitin (Ub)-binding site. This blockage likely prevented Ub from entering the active site of Uch37 and might form the basis of auto-inhibition. To understand the mode of auto-inhibition clearly and shed light on the activation mechanism of Uch37 by Rpn13, we investigated the Uch37-Rpn13 complex using a combination of mutagenesis, biochemical, NMR, and small-angle X-ray scattering (SAXS) techniques. Our results also proved that Uch37 oligomerized in solution and had very low activity against the fluorogenic substrate ubiquitin-7-amino-4-methylcoumarin (Ub-AMC) of de-ubiquitinating enzymes. Uch37Δ Hb, Hc, KEKE, a truncation removal of the C-terminal extension region (residues 256–329) converted oligomeric Uch37 into a monomeric form that exhibited iso-peptidase activity comparable to that of a truncation-containing the Uch37 catalytic domain only. We also demonstrated that Rpn13C (Rpn13 residues 270–407) could disrupt the oligomerization of Uch37 by sequestering Uch37 and forming a Uch37-Rpn13 complex. Uch37 was activated in such a complex, exhibiting 12-fold-higher activity than Uch37 alone. Time-resolved SAXS (TR-SAXS) and FRET experiments supported the proposed mode of auto-inhibition and the activation mechanism of Uch37 by Rpn13. Rpn13 activated Uch37 by forming a 1:1 stoichiometric complex in which the active site of Uch37 was accessible to Ub.